New species of Ptychozoon (Sauria: Gekkonidae) from the Nicobar Archipelago, Indian Ocean - Das, I.; Vijayakumar, S.P (Zootaxa, 2009)
A new species of Ptychozoon is described from the central portion of the Nicobar Archipelago, Bay of Bengal, India. It has been formerly referred to P. kuhli, a species widely distributed in Sundaland. Ptychozoon nicobarensis sp. nov. reaches an SVL of 100.3 mm, and is diagnosable from congeneric species in showing the following combination of characters: dorsum with a tan vertebral stripe, lacking dark transverse bars; supranasals in contact; cutaneous expansionson sides of head; absence of predigital notch in preantebrachial cutaneous expansion; imbricate parachute support scales; four irregular rows of low, rounded enlarged scales on dorsum; 20–29 scales across widest portion of tail terminus; three indistinct chevrons on dorsum; 7–11 pairs of preanal pores; femoral pores absent; tail with an expanded terminal flap and weak lobe fusion at proximal border of tail terminus.